The Monitoring System Architecture Development (Journal of Universal Science Research, 2024)
To implement the principles of the IoT concept, many production facilities must be re-equipped. Some of them must completely replace all existing equipment with new ones. This leads to significant costs. However, it is possible to develop external monitoring systems that, when connected to existing equipment, greatly expand the capabilities of the equipment. This allows you to modernize existing equipment and introduce IoT principles into production. In this article, the authors present the development of such a monitoring system for production.